O DICIONÁRIO COMO MATERIAL DIDÁTICO NA AULA DE LÍNGUA ESTRANGEIRA - Höfling, Camila; Silva, Maria Cristina Parreira da; Tosqui, Patrícia (Intercâmbio, 2010)
This paper presents a methodology about how to use a dictionary as a pedagogic resource in the foreign language class. Using some techniques/instructions, teachers can profit from this material in their classes and provide guidance for their students about which dictionary to choose and how to use it efficiently.